Interactive Effects of Apolipoprotein E ε4 and Triiodothyronine on Memory Performance in Patients With Subjective Cognitive Decline - Lee, Jin San; Soh, Yunsoo; Kim, Hyug-Gi; Lee, Kyung Mi; Kwon, Young Nam; Yoon, Sung Sang; Park, Key-Chung; Rhee, Hak Young (Frontiers in Medicine, 2020)
Background: The objective of the study was to investigate the associations between thyroid hormones, cognitive performance, and apolipoprotein E (APOE) genotype in euthyroid patients with subjective cognitive decline (SCD). Methods: A total of 197 patients with SCD who had no objective cognitive dysfunction on detailed neuropsychological testing and underwent thyroid function tests and APOE genotyping were included in this study. All participants were clinically euthyroid. Participants with at least one APOE ε4 allele were identified as APOE ε4 carriers, and participants with ε2/ε2, ε2/ε3, and ε3/ε3 genotypes were identified as APOE ε4 non-carriers. Pearson’s correlation and multiple linear regression analyses were performed to investigate the associations between neuropsychological performances and thyroid hormones as well as thyroid-stimulating hormone in APOE ε4 non-carriers and carriers. Results: There were no significant differences in neuropsychological performances between APOE ε4 non-carriers and carriers. The levels of triiodothyronine (T3) correlated positively with memory performances in APOE ε4 carriers, whereas a negative correlation was found in APOE ε4 non-carriers. There were significant interactive effects of APOE ε4 status and T3 level on the Seoul Verbal Learning Test immediate (p = 0.032) and delayed recall (p = 0.004) tasks. Conclusions: In patients with SCD, we suggested that T3 might have a protective effect on memory in those who are APOE ε4 carriers. The differential susceptibility hypothesis would support a gene-by-hormone crossover interaction between APOE ε4 allele and T3 in this study. Early identification and intervention of high-risk individuals for cognitive decline may be important to establish new strategies for preventing dementia.